Diary of a Wimpy Kid : Greg Heffley's Journal - Kinney, Jeff (UK Puffin Books, 2015)
Greg Heffley finds himself thrust into a new year and a new school where undersize weaklings share the corridors with kids who are taller, meaner and already shaving. Desperate to prove his new found maturity, which only going up a grade can bring, Greg is happy to have his not-quite-so-cool sidekick, Rowley, along for the ride. But when Rowley's star starts to rise, Greg tries to use his best friend's popularity to his own advantage.
Include Illustration
Keywords: Friendship -- Juvenile fiction. -- Friendship